Evaluasi Pengelolaan Program Ekstrakurikuler Pramuka untuk Pengembangan Soft Skill Siswa di Madrasah Tarbiyah Islamiyah Paninggahan - Yanova, Ekrita; Suprtaman, Suprtaman (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to evaluate the effectiveness of the Scouting extracurricular programme in supporting the development of students' soft skills at Madrasah Tarbiyah Islamiyah Paninggahan. The study uses a programme evaluation approach by combining the CIPP model, which covers context, input, process, and product, and the Discrepancy Evaluation Model (DEM) to identify the suitability between programme planning and implementation. The aspects evaluated include the formulation of program objectives, resource readiness, implementation mechanisms, student participation levels, and the impact of the program on the development of non-academic competencies. The results show that well-planned, structured, and sustainably implemented program management contributes positively to the improvement of students' soft skills, particularly in leadership, communication, cooperation, discipline, and creativity. These findings confirm that the success of soft skills development in madrasahs is greatly influenced by the effectiveness of programme management and the integration of religious values in every Scouting activity.